2017
DOI: 10.1177/0011000017699529
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Sociopolitical Engagement Among Lesbian, Gay, and Bisexual Racial/Ethnic Minority Adults

Abstract: Experiences of discrimination due to one's racial; ethnic; or lesbian gay, or bisexual (LGB) status have been associated with higher levels of sociopolitical involvement in racial, ethnic, and sexual minority communities. In this study, we examined (a) the associations between perceived racism in the LGB community, sociopolitical involvement in LGB racial or ethnic minority communities, and outness; and (b) whether the association between perceived racism and sociopolitical involvement in the LGB community is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(124 reference statements)
1
18
0
Order By: Relevance
“…DeBlaere and colleagues (2013) found that queer women of color may mitigate psychological distress related to perceived heterosexism through partaking in sexual‐minority based collective action. Similarly, a higher perception of racism in the mainstream queer community was associated with higher sociopolitical involvement in both queer and racial–ethnic minority communities (VanDaalen & Santos, ). Among same gender loving Black women and men, perceived connection to the queer community was a distinctly important predictor of sociopolitical action within both queer and Black communities (Harris & Battle, ; Battle & Harris, ).…”
Section: Introductionmentioning
confidence: 99%
“…DeBlaere and colleagues (2013) found that queer women of color may mitigate psychological distress related to perceived heterosexism through partaking in sexual‐minority based collective action. Similarly, a higher perception of racism in the mainstream queer community was associated with higher sociopolitical involvement in both queer and racial–ethnic minority communities (VanDaalen & Santos, ). Among same gender loving Black women and men, perceived connection to the queer community was a distinctly important predictor of sociopolitical action within both queer and Black communities (Harris & Battle, ; Battle & Harris, ).…”
Section: Introductionmentioning
confidence: 99%
“…Those studies that have examined civic participation among sexual minorities of color, however, provide suggestive evidence that their intersectionally-marginalized status is related to even more politically-distinctive behavior. Work by scholars such as Angelique Harris and Juan Battle (2013), Dara Strolovitch, Janelle Wong, and Andrew Proctor (2017), and Rachel VanDaalen and Carlos Santos (2017), for example, suggests that multiply marginalized individuals might be particularly socially and politically engaged, and also provides hints about the nature of that engagement. For example, Harris and Battle (2013) have shown that among “same-gender loving” Black women and men, feeling connected to LGBT communities was the most important predictor of sociopolitical involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Harris and Battle (2013) have shown that among “same-gender loving” Black women and men, feeling connected to LGBT communities was the most important predictor of sociopolitical involvement. While Harris and Battle find that a sense of community increases political engagement, scholars have found that some kinds of threats—such as the perception that heterosexism (Swank and Fahs, 2013) and racism (VanDaalen and Santos, 2017) are problems—is associated with increased political involvement, in the former case, among LGBT people of all races and in the latter case among LGBT people of color.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, activism was also related to psychological well‐being among White college students (Klar & Kasser, 2009), although the link for racial–ethnic minorities was less clear depending on whether engagement of activism was low‐ or high‐risk (e.g., Klar & Kasser, 2009; VanDaalen & Santos, 2017). Also, in a national survey of Black American adults, Seaton et al.…”
Section: Introductionmentioning
confidence: 99%